PENGARUH KOMPETENSI PEDAGOGIK GURU PAK TERHADAP RANAH KOGNITIF SISWA KELAS XSMK NEGERI 1 PANGARIBUAN - rusenna silitonga (IAKN Tarutung, 2020)
Rusenna SilitongaInstitut Agama Kristen Negeri (IAKN)TarutungRusennasilitonga38@gmail.com AbstractThis research aims to determine whether the influence of pedagogic competence by PAK teachers on the cognitive realm of grade X students SMK Negeri 1 Pangaribuan year of learning 2019/2020. Research hypothesis is that there is a positive and significant influence between the pedagogic competence by PAK teacher on the cognitive realm of grade X students SMK Negeri 1 Pangaribuan year of learning 2019/2020.This research is a correlational study using the descriptive and inferential statistical techniques. The population is the entire class of X S MK Negeri 1 Pangaribuan, a Christian Protestant number of 144 people. Sampling using the Random Sampling technique of 25% of the population is 36 people. The research instrument is a closed poll. Analysis result of value of Rxy = 0,548 Rtabel = 0,329 and Thitung = 3,820 Ttabel = 2,042 indicates that there is a relationship between pedagogic competence by Guru PAK to the cognitive realm of grade X students SMK Negeri 1 year of learning 2019/2020 and obtaining a sense of simple regression equation is.Hypothesis Test Obtained fcount = 14,682 Ftabel = 2.09 then H0 is rejected and Ha accepted. This research concluded that there is a positive and significant influence between the pedagogic competence by PAK teacher on the cognitive realm of grade X students SMK Negeri 1 Pangaribuan year of learning 2019/2020 of 30.03%. In connection with the results of this study, the authors provide input materials for PAK teachers to improve the cognitive realm of students.. Keyword: pedagogic competence by PAK Guru, student cognitive realm.